Documentation of individual-level social determinants of health among adults diagnosed with cancer in the United States - Hsu, Chia-Yun; Henderson, Gabriel; Slejko, Julia F.; Hussain, Arif; Swain, Richard Scott; Kalesan, Bindu; Huang, Pei-Lin; Onukwugha, Eberechukwu (Scientific reports, 2025)
The ICD-10-CM diagnosis codes ranging from Z55 to Z65 (Z codes) capture individual-level social determinants of health (SDOH) and are typically under-coded in individuals’ health records. There is limited characterization of SDOH Z codes among adults diagnosed with cancer and information about oncologists’ perspectives on Z codes. Using pooled cross sections, we selected 35,099 adults from the IQVIA PharMetrics ® Plus for Academics data and 17,852 individuals from linked cancer registry and claims data. The prevalence of comorbidities and metastatic cancer was higher among individuals with Z codes compared to those without Z code claims. The proportion of individuals with any Z code claims ranged from 0.6 to 0.9% in the PharMetrics Plus data and from 1.4 to 2.1% in the linked data. Among 112 medical oncologists/hematologists who responded to a survey about SDOH Z codes, 54% had not heard of Z codes to document SDOH. 26% reported that lack of reimbursement makes it difficult to increase their documentation and 64% would consider using Z codes if they are tied to payer reimbursement. Individuals with Z codes had greater comorbidity and cancer burden. Additional research is needed and depends on improved coding of SDOH Z codes.